2023
DOI: 10.1186/s12951-023-02122-8
|View full text |Cite
|
Sign up to set email alerts
|

Targeting and repolarizing M2-like tumor-associated macrophage-mediated MR imaging and tumor immunotherapy by biomimetic nanoparticles

Lijuan Chong,
Yao-Wen Jiang,
Dongxu Wang
et al.

Abstract: Anti-tumor M1-like and pro-tumor M2-like tumor-associated macrophages (TAMs) coexist in tumor microenvironments (TME). The adverse effects of these M1/M2 subsets on tumors directly affect the current strategies to improve anti-tumor immune response. Therefore, it has attracted great attention to change the tumor immunosuppressive microenvironment by reprogramming TAMs. In this paper, we constructed biomimetic nanoparticles (HMMDN-Met@PM) targeting M2-like TAMs for macrophage re-polarization. In detail, the cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 47 publications
0
1
0
Order By: Relevance
“…By stimulating the differentiation of tumor-associated macrophages (TAM) and modifying TME, NPC2 may improve the prognosis of human glioblastoma (GBM) [ 25 ]. TAM inhibits the invasion of tumor T cells, which in turn promotes the metastasis of LUAD [ 26 ]. In vitro, we found that KCNE1, NPC2, and SFTPD are lowly expressed in malignant epithelial, and the proliferation and invasion capacity of cells was inhibited after over-expression.…”
Section: Discussionmentioning
confidence: 99%
“…By stimulating the differentiation of tumor-associated macrophages (TAM) and modifying TME, NPC2 may improve the prognosis of human glioblastoma (GBM) [ 25 ]. TAM inhibits the invasion of tumor T cells, which in turn promotes the metastasis of LUAD [ 26 ]. In vitro, we found that KCNE1, NPC2, and SFTPD are lowly expressed in malignant epithelial, and the proliferation and invasion capacity of cells was inhibited after over-expression.…”
Section: Discussionmentioning
confidence: 99%